Adoption and Use of Social Media Platforms by Ophthalmology Programs during the COVID-19 Pandemic - Al-khersan, Hasenin; Tanenbaum, Rebecca; Kunkler, Anne L.; Patel, Nimesh A.; Sridhar, Jayanth (Journal of Academic Ophthalmology, 2022)
Purpose The aim of this study was to determine whether the coronavirus disease 2019 (COVID-19) pandemic influenced the presence of ophthalmology residency programs on social media platforms.Methods The presence of all accredited ophthalmology residency programs on Twitter and Instagram was assessed for January 2020 and August through March 2021 through an online search. The number of followers and posts per month during these periods was collected for each program. The presence of programs on social media was compared between the two time periods.Results The percentage of programs on Instagram rose from 18% in January of 2020 to 57% in March of 2021 (p < 0.001). On Twitter, the percentage of programs rose from 24 to 37% (p < 0.001). From January 2020 to March 2021, the mean number of Instagram followers increased from 265 to 649 (p < 0.0001), while the mean number of Twitter followers increased from 421 to 532 (p < 0.0001). The top ten ophthalmology residency programs in 2021 according to Doximity all had Instagram pages, while 57 (53%) of remaining programs had pages (p = 0.005). Meanwhile, 7 top ten programs (70%) were on Twitter compared with 36 (34%) of the remaining programs (p = 0.036).Conclusions The presence of ophthalmology residency programs on Instagram and Twitter increased significantly after the onset of the COVID-19 pandemic. Social media represents an evolving platform through which programs can connect with prospective residents.
Keywords: social media; medical education; COVID-19